Appraisal of the impact of a community-driven development project (Fadama II) in Adamawa state, Nigeria - Umar Adamu, Madu (Universiti Malaysia Sarawak, (UNIMAS), 2013)
The community-driven development (CDD) approach has increasingly become fashionable due to its impending capabilities to develop projects that are sustainable, receptive to local priorities, empower local communities and targeting of the poor and vulnerable groups. The purpose of this study is to assess the impact of Fadama II project, which is a CDD project and the first of its kind in Nigeria. It is also the largest agricultural and rural development project in Nigeria. The project focused on increasing the incomes of Fadama Users on sustainable basis via empowerment in terms of capacity building, advisory services, acquisition of productive assets and rural infrastructure development. This study used propensity score matching (PSM) to select 300 comparable project beneficiaries and non-beneficiaries. The study also used double difference methods to compare the impact indicators. T-test analysis was used to compare means and determine impact of the project apart from descriptive statistics used. Net Present Value (NPV) was also used to determine economic viability of the productive assets acquired. The results show that Fadama II project succeeded in targeting the poor and women farmers in its activities. Participation in the project also increased the income of beneficiaries by about 60.8 percent, which is well above the targeted increase of only 20 percent in the six years period of the project. Fadama II has as well successfully implemented its CDD approach, as community members were given voice to decide for the planning and implementation of projects meant to touch their lives. The value of productive assets has increased significantly among the beneficiaries. The value of group assets increased more than individual assets. Regarding rural infrastructure investments, Fadama II project had positive impacts on beneficiaries’ access to market and reduced transportation cost. The study also revealed surprising effects on beneficiaries’ commercial behavior and statistically significant impacts on nonfarm activities. The study observed that Fadama II increased the demand for postharvest handling and marketing information technologies but did not have a significant impact on the demand for financial management. Fadama II reduced the demand for soil fertility management technologies. The decline likely reflects the project’s focus on providing post-production advisory services and suggests the need for the project to increase its support for soil fertility management and thus vi limit the potential for land degradation resulting from increased agricultural production. Conflict has been reduced among the community members as a result of participation. The findings have also revealed that the project has enhanced the capacities of the beneficiaries to cope with their activities. The project has also succeeded in targeting the poor and vulnerable groups and increased short-term household incomes among the core poor group significantly. The unique feature that could have contributed to the significant impact of the project in a short time is its participatory and demand driven approach that gives voice to the communities. It is also attributed to its broad-based strategy of using CDD model, which addresses the major constraints limiting the success of projects that do not take into consideration the interest of the community members. It is concluded therefore, that the strategy of participatory and demand-driven development should take a centre stage in any rural development process. This has implications on planning poverty reduction efforts in low-income countries. CDD project that simultaneously considers communities’ demand and addresses many constraints will likely build synergies that will lead to larger impacts than will a top-down project. This suggests the need for the government and donors to pool resources and initiate multipronged CDD projects rather than many isolated and service oriented projects.